Utilization Iron Filings and Microwave Heating in Roughening the Surface of Smoothed Coarse Aggregates - Mohammed Ridha Mahmmod Wajde, Laith; S. Alyhya Zainab, S.; R. Abdul Rasoul, M.; T. Abdulrasool, Abdulrasool; ., . (International Journal of Engineering and Technology, 2018)
Properties of coarse aggregate such as texture have a significant influence on the performance of fresh and hardened concrete. A smooth surface can enhance workability, yet a rougher one offers a stronger bond between aggregate and paste, resulting in higher strength. This research aims to roughen the texture of white smoothed aggregate by using cement-iron filings mortar with the aid of microwave maturation to accelerate the adhesion process of mortar-aggregate surface. The mortar was prepared by mixing an equal weight of cement and iron filings, of a particular size, with sand. Four different periods (2, 4, 6 and 8 mints.)  of microwave treatment in addition to water curing were considered plus one reference mortar which cured in only air for 24 hrs. The treated aggregate was then used for casting concrete specimens with a w/c ratio of 0.5 in which their properties being determined by means of density, compressive and tensile strengths observations. The main findings revealed that the concrete specimens contained microwave treated aggregate attained higher compressive strength compared with those treated in the air. Data also showed that concrete specimens with microwave treated aggregate possess better tensile properties as a consequence of the improvement in the transition zone.
Keywords: Coarse aggregate; Compressive strength; Iron filings; Microwave; Tensile strength; Texture.